Assessment of Animal-Based Pig Welfare Outcomes on Farm and at the Abattoir: A Case Study - Teixeira, Dayane Lemos; Salazar, Laura C.; Enriquez-Hidalgo, Daniel; Boyle, Laura A. (Frontiers in Veterinary Science, 2020)
The study assessed the prevalence of animal-based pig welfare outcomes on one Chilean farm and one abattoir. A total of 198 pens of slaughter pigs (9,049 pigs) were observed on farm and 54 batches (8,843 pigs) were observed at the abattoir. All assessments were conducted from outside the pen on farm and from outside the corridor where pigs were unloaded from the truck at the abattoir. Batch size and number of pigs with ear, tail and skin lesions, hernias, rectal prolapse, bursitis and lameness were recorded. Data were analysed using generalised linear mixed models. There was a large variation among pens on farm and among batches at the abattoir for all outcomes. Bursitis was the most prevalent outcome recorded in both locations, followed by ear lesions recorded on farm and by tail lesions recorded at the abattoir. Ear lesions’ prevalence was higher on farm (P < 0.001), while tail lesions, hernia and bursitis prevalence were higher at the abattoir (P < 0.001). Ear lesions’ prevalence on farm was higher in female and mixed-sex groups than in male groups (P < 0.01), but male groups tended to have a higher tail lesions’ prevalence (P < 0.1). The results show a difference in welfare outcomes, suggesting that assessment of outcomes on farm could complement ante-mortem inspections at the abattoir. However as the same animals were not inspected in the two locations and the possibility of seasonality influence on the results, the findings should be interpreted with caution and further research is required.